NEST and EGGS of THE MARSH ANTWREN (STYMPHALORNIS ACUTIROSTRIS): THE ONLY MARSH-DWELLING THAMNOPHILID - Reinert, Bianca L.; Belmonte-Lopes, Ricardo; Bornschein, Marcos R.; Sobotka, Daiane D.; Correa, Leandro; Pie, Marcio R.; Pizo, Marco A. [UNESP] (Wilson Ornithological Soc, 2012)
We describe the nest and eggs of the Marsh Antwren (Stymphalornis acutirostris), a recently described species which is the only member of the Thamnophilidae restricted to marsh habitats. We conducted 1,560 hrs of nest searching in tidal marshes of southern Brazil and found 178 nests. All nests were of dry fibers, straws, and silk. Nineteen plant species were used for nest attachment. All nests had a clutch of two white eggs with several irregular brown spots scattered over the entire egg, concentrated at the middle or the largest pole. The strategy of nest attachment to vertical structures used by the Marsh Antwren was previously unknown in the Thamnophilidae. Received 14 June 2011. Accepted 12 December 2011.